Agricultural economy and trade of Spain - United States. Department of Agriculture. Economic Research Service (Wasington. D.C. : Department of Agriculture. Economic Research Service, 1972)
This report discusses the growth of agricultural economy and trade of Spain in the l960's (compared with the general economy), perennial problems impeding progress in the four areas of development, and prospects for solving these problems.
lje 05/07/2017
Loans
Keywords: Lopez, J; Agriculture -- Economic aspects; Agriculture; Spain